2020
DOI: 10.1371/journal.pone.0243886
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation and resilience of commercial fishers in the Northeast United States during the early stages of the COVID-19 pandemic

Abstract: Commercial fisheries globally experienced numerous and significant perturbations during the early months of the COVID-19 pandemic, affecting the livelihoods of millions of fishers worldwide. In the Northeast United States, fishers grappled with low prices and disruptions to export and domestic markets, leaving many tied to the dock, while others found ways to adapt to the changing circumstances brought about by the pandemic. This paper investigates the short-term impacts of the early months of the COVID-19 pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 50 publications
3
60
0
2
Order By: Relevance
“…Our research provides evidence of a temporary re-localization in the seafood system during the early months of the COVID-19 pandemic, in which demand for local and directly sourced seafood spiked abruptly. This finding is consistent with recent studies that find evidence that fishers shifted to local and direct sales as a key adaptation strategy during the early months of the pandemic (Pita, 2020;Smith et al, 2021). To date, ASNs have been described as an important strategy for small-and midsize seafood operations to build firm-level resilience (Kittinger et al, 2015;Stoll et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our research provides evidence of a temporary re-localization in the seafood system during the early months of the COVID-19 pandemic, in which demand for local and directly sourced seafood spiked abruptly. This finding is consistent with recent studies that find evidence that fishers shifted to local and direct sales as a key adaptation strategy during the early months of the pandemic (Pita, 2020;Smith et al, 2021). To date, ASNs have been described as an important strategy for small-and midsize seafood operations to build firm-level resilience (Kittinger et al, 2015;Stoll et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…Alternative seafood networks exist worldwide and were identified as a "bright spot" in both high-and low-income countries during the early months of the COVID-19 pandemic (Bennett et al, 2020;Gephart et al, 2020;Loring et al, 2020;O'Malley, 2020). For example, in the northeast, United States, Smith et al (2021) found that 60% of the 258 fishers they surveyed reported adapting to local and direct seafood sales during the pandemic. Similarly, in a survey of small-scale fisheries across Europe from more than 105 fishing organizations from 12 countries, Pita (2020) found that 48% of respondents had shifted to direct-to-consumer sales through ASNs.…”
Section: Alternative Seafood Network Contribute To Systemic Resiliencementioning
confidence: 99%
“…Coping and adaptive measures represent early responses during the first five months of the COVID-19 pandemic. Others have identified adaptations such as switching species harvested, selling to alternate markets, supplementing income from other sources, or temporarily stop fishing ( Smith et al, 2020 ). Short-term coping will remain important as the pandemic spreads and re-emerges in countries.…”
Section: Resultsmentioning
confidence: 99%
“… Immediate research needs: To complement price and production data, use survey tools to document and better understand COVID-19 impacts on people working at all levels in seafood value chains and seafood consumers in order to direct support to vulnerable actors in the seafood system. Examples of this work include: ( Smith et al, 2020 ; Rosen, 2020 ; van Senten ; Kumaran et al, 2020 ; Campbell et al, 2020 ; Seshagiri et al et al ; Giannakis et al, 2020 ; Steenbergen et al, 2020 ; Sorensen et al, 2020 ) Document and share case-experiences of actors in the value chain that have adapted to shifts in supply and demand of seafood so lessons from their strategies can be more widely adopted. Examples of this work include: ( Stoll et al, 2020 ; Smith et al, 2020 ) Improve open data and data sharing platforms to facilitate the exchange of information about the societal impacts of COVID-19, to enable more rapid and coordinated responses to future shocks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation